Intercommunity Development Associations in Romania. A lost opportunity? - Cosmin CHIRIAC; Constantin-Vasile ȚOCA (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The Intercommunity Development Associations (IDA) were introduced in Romania with the purpose of covering the need of local or county territorial administrative units (TAU) to implement common development projects that would benefit the communities of multiple territorial units. The need was especially greater in the case of rural local territorial administrative units, that have a limited financial power, while also being part of a very fragmented administrative level. Thus, the development of larger projects is impossible for some TAUs on their own. The objective of this research is to analyse the IDAs created so far in the Bihor County, considering the legislation that made them possible was introduced almost 20 years ago, even if some associations predate this legislation. The purpose is to understand if there are certain aspects that favour their establishment, without focusing on their activity. Through this study, we are putting together a methodology that will be applied to the entire country, to understand whether our findings for the Bihor County can be applied to other counties as well.